PENERAPAN POLA ASUH DEMOKRATIS ORANG TUA UNTUK MEMINIMALISIR KENAKALAN REMAJA - Muhamad Rangga; Wahyu Hidayat; Dinno Mulyono (Comm-Edu (Community Education Journal), 2026)
This study aims to describe the implementation of democratic parenting by parents in minimizing juvenile delinquency in RT 03 RW 04, Cicangkang Girang Village, Sindangkerta District, West Bandung Regency. The phenomenon of juvenile delinquency in this area appears in the form of undisciplined behavior, lack of responsibility, and a tendency to violate social norms. Through the application of democratic parenting, parents are expected to instill values of responsibility, discipline, and open communication within the family. This research employed a qualitative descriptive approach involving 15 parents who have adolescent children, selected using purposive sampling techniques. Data were collected through observation, interviews, and questionnaires, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results indicate that democratic parenting is implemented through two-way communication, shared responsibility, and parental role modeling. This parenting style positively influences the reduction of juvenile delinquent behavior, as evidenced by improved discipline, adherence to social norms, and mutual respect within families. Therefore, the implementation of democratic parenting proves effective as a form of family-based education in preventing juvenile delinquency in community environments.